Comparison of the effects of sedation and general anesthesia in surgically assisted rapid palatal expansion - (:unkn) unknown (SAUDI MED J, 2011)
Objectives: To compare the effects of sedation and general anesthesia for surgically assisted rapid palatal expansion (SARPE). Methods: This randomized prospective study included 30 patients who were scheduled for SARPE performed between January 2008 to February 2010 in the Department of Oral and Maxillofacial Surgery, Faculty of Dentistry, Marmara University, Istanbul, Turkey. Patients were allocated into Group S - midazolam + fentanyl sedation (n=15), and Group G - general anesthesia (n=15). Hemodynamic parameters, duration of anesthesia, surgery, recovery time, time to discharge, visual analogue scale (VAS) pain scores at 30 minutes (min), one hour (hr), 4 hours, 12 hours, and 24 hours, first consumption of analgesic time, total amount of consumption of analgesics, patient and surgeon satisfaction, nausea, and vomiting were recorded. Results: Analgesic time was significantly longer in Group S (p=0.008), and total analgesic consumption was significantly lower in Group S than in Group G (p=0.031). Patient satisfaction was statistically higher in Group S (p=0.035). At 30 min, one hr, and 12 hrs, VAS satisfaction scores in Group S were statistically lower than those in Group G, and at 4 hrs and 24 hrs there was no statistical difference in VAS scores for both groups. Conclusion: The use of sedation for outpatient SARPE resulted in lower pain scores at discharge, lower analgesic consumption, and greater patient satisfaction.
Keywords: INTRAVENOUS SEDATION; CONSCIOUS SEDATION; RISK-FACTORS; SURGERY; CHILDREN